Case report: Laparoscopic approach in the treatment of presacral lipoma. (November 2018) - Poskus, Eligijus; Makunaite, Gabija; Kubiliute, Ieva; Danys, Donatas
Abstract: Retrorectal lipoma, as well as other retrorectal tumours, is a relatively rare disorder. Retrorectal tumours accounted for 1 in 40, 000 hospital admissions. We present a case of retrorectal lipoma, 15 cm × 10 cm × 8 cm in size, treated by the laparoscopic approach. The preoperative magnetic resonance imaging visualised a mass, 12 cm × 6.7 cm × 8.6 cm in diameter, in the retrorectal space, spreading toward the left obturator foramen. Surgery was indicated due to exclude malignant process certainly, because it is difficult to differentiate lipoma from low-grade liposarcoma on non invasive imaging. Laparoscopic extirpation of the tumour was performed. The overall operative time was 80 min. The diagnosis of lipoma was established on histological examination. The patient was discharged from hospital on the 2nd day after the surgery. We have found this minimally invasive operation to be an effective and well-tolerated treatment option, determined by the experience of the surgeon. Highlights: Retrorectal lipoma is a benign mesenchymal tumour composed of mature adipose tissue, located in the retrorectal space [1 ]. Retrorectal tumours in adults are rare [3–9 ], Jao et al. found that retrorectal tumours accounted for 1 in 40, 000 hospital admissions [5 ]. Miscellaneous, non classified tumours account for 10–25% of all retrorectal tumors. Retrorectal lipomas are included in this group [4, 7 ]. These tumours usually affect middle-aged patients and occurs twice as often in women as in men [7 ]. Retrorectal lipomas, as well as other benign retrorectal tumours, are often completely asymptomatic [4, 6, 8, 9 ]. They are usually found incidentally when performing a pelvic or rectal examination [4, 9 ]. Retrorectal lipomas also might give nonspecific symptoms, mostly from the compression of pelvic structures, viscera and nerves. Symptoms depend on the size of the tumour, its localisation, extension [3 ]. Diagnosis and treatment of retrorectal tumours, including lipomas, remain difficult. Currently, computed tomography scan used in conjunction with magnetic resonance imaging scan is the gold standard in diagnosing retrorectal tumours [4 ]. These methods are used to find out the size, structure of the tumour, its relationship with surrounding organs that is a necessary information for planning surgical approach [3, 4, 8 ]. Biopsy should not be performed before a surgery [5, 6 ]. All retrorectal tumours, including lipomas, should be resected [3, 6, 7 ]. In the presenting case laparoscopic surgery was indicated due to exclude malignant process, because it is difficult to differentiate lipoma from low-grade liposarcoma on magnetic resonance imaging [10 ].